Pengaruh Komitmen dan Kompensasi terhadap Kinerja Dosen pada Perguruan Tinggi Swasta (PTS) - Rully Armanto; Muji Gunarto (MBIA, 2020)
This study aims to determine the effect of commitment and compensation on lecturer performance in private universities (PTS). The performance of lecturers in Indonesia, especially in PTS, is still considered unsatisfactory when compared to lecturers in state universities (PTN). The main factor that is suspected to be the cause is the commitment of the foundation as the owner and leader of the higher education institution as the manager and the compensation which is still low. The research sample was the permanent lecturers of the foundation at PTS in Palembang, totaling 44 respondents. The sampling technique used is cluster random sampling at Universities, Colleges, Academies, and Polytechnics. The statistical analysis technique used multiple regression analysis with the help of SPSS software. The results showed that commitment and compensation had a significant effect on the performance of lecturers at private universities in Palembang City. The most dominant factor in the performance of PTS lecturers in Palembang City is compensation, meaning that by increasing the compensation for lecturers, their performance will increase. The results of this study really provide input for the improvement of private universities in Palembang City because when viewed from the permanent income of private universities in Palembang City, it is still below the average decent income of a lecturer. Abstrak Penelitian ini bertujuan untuk mengetahui pengaruh komitmen dan kompensasi terhadap kinerja dosen pada Perguruan Tinggi Swasta (PTS). Kinerja dosen di Indonesia khususnya di PTS masih dirasa belum memuaskan jika dibandingkan dengan dosen di Perguruan Tinggi negeri (PTN). Faktor utama yang diduga menjadi penyebabnya adalah komitmen yayasan sebagai pemilik dan pimpinan perguruan tinggi sebagai pengelola serta kompensasi yang dirasa masih rendah. Sampel penelitian adalah dosen tetap yayasan pada PTS di Kota Palembang yang berjumlah 44 orang responden. Teknik sampling yang digunakan adalah cluster random sampling pada Universitas, Sekolah Tinggi, Akademi dan Politeknik. Teknik analisis statistik digunakan analisis regresi berganda dengan bantuan software SPSS. Hasil penelitian menunjukkan bahwa komitmen dan kompensasi berpengaruh signifikan terhadap kinerja dosen pada PTS di Kota Palembang. Faktor yang paling dominan terhadap kinerja dosen PTS di Kota Palembang adalah kompensasi, artinya bahwa dengan meningkatnya kompensasi bagi dosen, maka kinerjanya akan meningkat. Hasil penelitian ini sangat memberikan masukan bagi perbaikan PTS di Kota Palembang karena jika dilihat dari pendapatan dosen tetap pada PTS di Kota Palembang masih dibawah rata-rata pendapatan layak seorang dosen.